Exploring Exercise Specificity in Powerlifting: A Survey of Powerlifters' Training Practices and Demographic Influences - Amdi, Christian H; Spence, Alyssa-Joy; Helms, Eric R; McGuigan, Michael R (Lippincott, Williams & Wilkins, 2025)
This study aimed to examine powerlifters' training practices related to exercise specificity. A total of 548 powerlifters responded to an anonymous online survey, with 401 completing all questions. On average, lifters trained 4.25 times per week and performed the competition-style squat, bench press, and deadlift 1.64, 2.48, and 1.37 times per week, respectively-typically using 1-7 repetitions at ratings of perceived exertion (RPEs) of 6-10. Almost all lifters (>97.5%) incorporated varied practice, including barbell variations (squat: 1.50×, bench press: 2.14×, deadlift: 1.26×) and accessory exercises (squat: 1.73×, bench press: 2.46×, deadlift: 1.72× per week). These were generally performed with 4-7 repetitions at RPE 6-8.5 for variations, and ≥8 repetitions at RPE 6-10 for accessories. The most common barbell variations involved slower eccentric phases, added or prolonged pauses in the bottom position, among others. Most lifters modified how they programmed (i.e., volume, frequency, relative-load, or RPEs) the competition lifts (88.2%), barbell variations (71.7%), and accessory exercises (62.3%) as competition approached, whereas 35.1-45.7% changed exercise selection depending on competition proximity. However, 49.0-58.7% maintained consistent exercise selection throughout competition periods. These programming decisions were influenced by athlete characteristics such as gender, use of supportive equipment, age, weight class, relative strength, and training status. Collectively, these findings indicate that varied practice is common in powerlifting.
Keywords: exercise selection; resistance training; variation; varied practice; 42 Health Sciences; 4207 Sports Science and Exercise; Physical Activity; 1106 Human Movement and Sports Sciences; 1116 Medical Physiology; Sport Sciences; 3202 Clinical sciences; 3208 Medical physiology; 4207 Sports science and exercise; Humans; Weight Lifting; Male; Adult; Female; Resistance Training; Young Adult; Physical Exertion; Athletic Performance; Surveys and Questionnaires; Middle Aged; Humans; Weight Lifting; Adult; Middle Aged; Female; Male; Athletic Performance; Physical Exertion; Resistance Training; Young Adult; Surveys and Questionnaires; Humans; Weight Lifting; Male; Adult; Female; Resistance Training; Young Adult; Physical Exertion; Athletic Performance; Surveys and Questionnaires; Middle Aged